The adoption of gamification in e-banking - Rodrigues, L. F.; Costa, C. J.; Oliveira, A. (ISDOC '13: Proceedings of the 2013 International Conference on Information Systems and Design of Communication, 2013)
The development of multiple web applications with features of video games gave way to a new trend called Gamification. However, there isn't a clear explanation that allows the connection of the elements of the game applications with non-game features, mainly in traditional highly regulated financial sector. The aim of this study is to investigate the acceptance of a business application Gamified in e-banking. Based on the Technology Acceptance Model (TAM), the results from an online survey of 183 customers show that the Gamified application had a positive impact on the acceptance of this new concept in e-banking. Our findings show that perceived ease-of-use have a strong positive influence on costumers intentions and on the perceived usefulness. Further analysis and model modification show that perceived usefulness and enjoyment have positive influence on perceived ease-of-use. The results also show that the customers have accepted and used the Gamified application to manage their investments and bought more mutual funds thus increasing the chance to win the game.